Introduction to LGBTQ+ : awareness : gender (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. In this track, we'll define some important terms relating to gender, explore the experiences of trans people in employment, and provide some practical information on how to make your workplace safer, more accessible and more inclusive for trans colleagues. Learning Objectives Learn some important terms relating to gender Learn about the experiences of trans people in employment Learn practical ways of making your workplace safer, more accessible and more inclusive for trans colleagues.